Criminal Settlement as a Judicial Solution in Iraq’s Legal Framework: Penyelesaian Pidana sebagai Solusi Yudisial dalam Kerangka Hukum Irak - Taqi, Riyadh Hussain (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Criminal settlement has emerged as a vital alternative to conventional criminal trials, offering procedural efficiency and fostering reconciliation. Specific Background: In Iraq, the practice has gained traction, yet its legislative and institutional frameworks remain underdeveloped. Knowledge Gap: Despite growing application, limited research exists on Iraq’s legal structure governing criminal settlements and its alignment with comparative international models. Aims: This study aims to critically examine the historical evolution and legal framework of criminal settlement in Iraq, assess its practical implications on judicial processes, and compare Iraq’s approach with selected Arab and global systems to propose reforms. Results: The findings indicate that criminal settlements enhance court efficiency, promote social harmony, and assist victim recovery; however, several procedural and regulatory deficiencies persist. Novelty: The study uniquely integrates doctrinal analysis, judicial review, and comparative law to uncover the systemic limitations of Iraq’s settlement procedures while incorporating restorative justice theory. Implications: The research advocates for establishing judicial reconciliation units, enhancing judge and prosecutor training, implementing public awareness campaigns, and restricting settlements in cases demanding public accountability. These reforms aim to institutionalize criminal settlement as a sustainable pillar of justice in Iraq. Highlights: Identifies legal gaps in Iraq’s criminal settlement system. Compares Iraq with Arab and global legal practices. Recommends reforms for justice, efficiency, and victim protection. Keywords: Criminal Settlement, Iraq, Comparative Law, Restorative Justice, Legal Reform